Experiences of some developing countries in the implementation process of developing science, technology and innovation strategy - Cao Thi Hong Ngoc; Le Ngoc My (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Over more than two phases of implementing the Science and Technology Development Strategy, which is currently the Science, technology and innovation Development Strategy until 2030, alongside positive outcomes contributing to national socio-economic development, the strategy implementation process has also revealed certain limitations and has yet to fully harness the potential of national science, technology and innovation. This paper presents research findings on the experiences from the strategy implementation processes of selected developing countries, such as Malaysia and India, to build practical foundations and provide insights and recommendations for the implementation of the strategy in Vietnam. The research materials used are secondary documents, gathered from both domestic and international published works, including specialized reports, scientific articles, periodic reports, etc. The article proposes a three-step process for implementing the Strategy for Science, Technology and Innovation Development: preparation; implementation; inspection, evaluation and adjustment. This is also the analytical framework to analyze the implementation process of the Strategy in Vietnam, Malaysia and India. Code: 24102401